Theoretical sociology : a concise introduction to twelve sociological theories - Turner, Jonathan H. (Sage, 2014)
"What can sociological theory tell us about the basic forces that shape our world? With clarity and authority, leading theorist Jonathan H. Turner seeks to answer this question through a brief, yet in-depth examination of twelve major sociological theories. Readers are given an opportunity to explore the foundational premise of each theory and key elements that make it distinctive. The book draws on biographical background, analysis of important works, historical influences, and other critical insights to help readers make the important connections between these monumental sociological theories and the social world in which we live. This concise resource is a perfect complement to any course that seeks to examine both classic and contemporary sociological theory."--Publisher's website.